The Role of Organizational Citizenship Behavior in Mediating Motivation, Discipline, and Organizational Culture on Employee Performance: A Study of Regional Water Companies in West Kalimantan - Yohanes Andriyus Wijaya; Ramadania Ramadania (MASI Mandiri Edukasi, 2026)
The role of Organisational Citizenship Behaviour (OCB) as a mediator of employee performance remains inconsistent, and research in the Indonesian public sector, particularly in West Kalimantan PDAM, remains limited. This study examines the role of Organisational Citizenship Behaviour (OCB) as a mediator in the relationships among motivation, discipline, organisational culture, and employee performance at Regional Water Companies (PDAMs) in West Kalimantan, Indonesia. Using Structural Equation Modelling-Partial Least Squares (SEM-PLS) with a sample of 110 employees from PDAM Tirta Pancur Aji, one of 13 PDAMs in West Kalimantan, this research addresses the research gap regarding the mediating role of OCB in public sector organisations. Results indicate that motivation, discipline, and organisational culture significantly influence both OCB and employee performance, with organisational culture exerting the strongest effect, followed by work motivation and work discipline. Furthermore, OCB partially mediates the relationships between these HR factors and employee performance. Research findings also show that OCB has the strongest direct impact on PDAM employee performance. These findings contribute to organisational behaviour theory in the public sector and offer practical implications for PDAM management to enhance service delivery and achieve the Sustainable Development Goals, particularly SDG 6 on clean water and sanitation.